PEGAS BELAJAR Application for Tracing Student’s Learning Styles In Senior High School - Ramli Ramli; Sulaiman Samad (Jurnal Psikologi Pendidikan dan Konseling: Jurnal Kajian Psikologi Pendidikan dan Bimbingan Konseling, 2020)
The research aims to determine 1) the description of the level of learning needs of the Learning Spring as a medium for tracing the learning styles of students in high schools, 2) the prototype of the Learning Spring as a medium for tracing the learning styles of students in high schools, and 3) the level of validity and practicality of Learning Spring as a medium for tracing. Student learning styles in high school. Using this type of development research with the ADDIE Model. Collecting data through interviews needs analysis questionnaires and trial questionnaires, with qualitative and quantitative data analysis. Trial phase with One to one Trial and Small Group Trial. The subject of validity testing to experts and practitioners and practicality test to teachers and students. The results showed 1) the level of need for Learning Spring as a medium for tracing student learning styles in high schools is in the high category, 2) the prototype Learning Spring as a medium for tracking student learning styles in high schools in the form of websites and guidebooks, and 3) validity The media through one to one trial to experts and practitioners shows a very high level of validity, the practicality of the media through a small group trial to teachers and students also shows a very high level of practicality. This shows that learning springs as a medium for tracing student learning styles have adequate content, presentation, language and graphic appropriateness.